Impacts of Cornerstone Reading Tutorial Program - Manug, Felisa; Rabia, Danesa; Manug, Ernesto; Aguanza, Aezel; Mante, Katrine Mae Baldero; Camargo, John Ferwin; Evardo, Mae; Rulida, Ernesto (International Journal For Research In Educational Studies, 2019)
This study aimed to evaluate the impacts of the Cornerstone Reading Tutorial Program conducted by the Bohol Island State University - Calape Campus, College of Teacher Education in Calape Central Elementary School, Calape, Bohol for the school year 2014-2016. This was done spearheaded by the Couples for Christ (CFC) - Answering the Cry of the Poor (ANCOP) in their program called “Building the Church of the Poor (BCOP) and the Department of Education. Study results showed that the tutorial program is effective in increasing the pupil’s reading proficiency level based on Dolch Basic Sight Vocabulary Test results and English performance based on English grades. Hereafter, the tutorial program produces positive impact to the students’ reading proficiency and English performance. Moreover, the reading proficiency level of the pupils are related to their English performance. The progress of the pupil’s reading proficiency level through the tutorial program will help them increase their English performance in school. Thus, the Cornerstone Reading Tutorial Program is much effective and must be done in the next years to help shape the mind of pupils, especially in the skill of reading.